2017
DOI: 10.1021/acs.jafc.7b02474
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, Translocation, Metabolism, and Distribution of Glyphosate in Nontarget Tea Plant (Camellia sinensis L.)

Abstract: The uptake, translocation, metabolism, and distribution behavior of glyphosate in nontarget tea plant were investigated. The negative effects appeared to grown tea saplings when the nutrient solution contained glyphosate above 200 mg L. Glyphosate was highest in the roots of the tea plant, where it was also metabolized to aminomethyl phosphonic acid (AMPA). The glyphosate and AMPA in the roots were transported through the xylem or phloem to the stems and leaves. The amount of AMPA in the entire tea plant was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…However, the study system utilized in this work is comparable to a spray application situation that has a risk of high herbicide delivery rate, regardless of the label recommendation. The uptake, translocation, and metabolism of glyphosate in nontarget tea plants were examined in a hydroponic system by Tong et al [68]. The highest content of glyphosate was observed in the plant roots, where it was also metabolized to AMPA.…”
Section: Glyphosate’s Effects On Crop Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the study system utilized in this work is comparable to a spray application situation that has a risk of high herbicide delivery rate, regardless of the label recommendation. The uptake, translocation, and metabolism of glyphosate in nontarget tea plants were examined in a hydroponic system by Tong et al [68]. The highest content of glyphosate was observed in the plant roots, where it was also metabolized to AMPA.…”
Section: Glyphosate’s Effects On Crop Healthmentioning
confidence: 99%
“…The glyphosate and its metabolite were transported from the roots through the xylem or phloem to the stems and leaves. The results from this study indicated that plant-available glyphosate could be continuously absorbed by roots, metabolized, and transported into edible tea leaves [68]. Glyphosate uptake into nontarget plants is suggested when the herbicide and its degradation products (e.g., AMPA) are found in plant tissues and seeds of crops like soybean and corn [69] and tree foliage [20] following application of glyphosate to manage weeds in farms and adjacent areas.…”
Section: Glyphosate’s Effects On Crop Healthmentioning
confidence: 99%
“…Various studies have shown that tea has numerous beneficial effects on health (Xu, Song, Li, & Wan, ). However, some risk chemicals in tea products may bring a health threat to tea drinkers, such as polycyclic aromatic hydrocarbons (PAHs; Lin, Tu, & Zhu, ), new pollutant—perchlorate (Lin, Lo, & Fuh, ), pesticides (Tong et al., ), and some risk elements like aluminum (Al), cadmium (Cd), manganese (Mn), lead (Pb), and copper (Cu; Dambiec, Polechońska, & Klink, ; Görür, Keser, Akçay, Dizman, and Okumuşoğlu, ; Wong, Zhang, Wong, & Lan, ).…”
Section: Introductionmentioning
confidence: 99%
“…To develop a protocol for detecting trace levels of target pesticide residues in fresh tea leaf, the extraction and clean-up method was optimized based on our previously published work. 22,23 One gram of untreated tea leaves was weighed out and spiked with pesticide standards to generate calibration curves, which were linear over the range 0.1-100 μg L −1 with correlation coefficients > 0.999 for the five target pesticides ( Table 1). The recovery rates ranged from 77% to 96%, with relative SD (n = 5) values ranging from 2% to 9% for acephate, trichlorfon, acetamiprid, imidacloprid and thiamethoxam at a spiked level of 0.0025 and 0.025 mg kg −1 .…”
Section: Methods Validationmentioning
confidence: 99%
“…Samples were processed as described in previous studies. 22,23 UPLC-MS/MS analysis An UPLC-electrospray ionization-tandem triple-quadrupole mass spectrometer was used to analyze the target compounds in positive ion mode. For LC analysis, a Waters Acquity UPLC System (Waters Corp., Milford, MA, USA) with a binary pump was used.…”
Section: Field Trials and Samplingmentioning
confidence: 99%